Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1021/ie501415b
|View full text |Cite
|
Sign up to set email alerts
|

Steady and Transient Characteristics of Catalytic Flow Reverse Reactor Integrated with Central Heat Exchanger

Abstract: A Pd/Al 2 O 3 monolith catalyst was prepared by wet impregnation. Its excellent performance was demonstrated in the removal of lean methane. After 1000 h of operation, a higher catalytic activity can be sustained. On this basis, a pilot-scale catalytic flow reversal reactor (CFRR) coupled with a central heat exchanger was designed for catalytic removal of ventilation air methane. Experiments showed high methane destruction ratios were achieved at elevated reactor temperatures maintained by reverse flow operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
(129 reference statements)
0
11
0
Order By: Relevance
“…As shown in Table 3, different types of catalysts have been studied in RFR, being Pd the most popular [41][42][43][44][45][46][47][48], the main reason being that Pd provides higher activity [49]. Kinetic studies on Pd-based catalysts showed a 0.5-1.0-order dependence for lower alkanes, whereas a very weak or zero-order dependence was observed for oxygen [50][51][52][53].…”
Section: Oxidation Of Methanementioning
confidence: 99%
See 4 more Smart Citations
“…As shown in Table 3, different types of catalysts have been studied in RFR, being Pd the most popular [41][42][43][44][45][46][47][48], the main reason being that Pd provides higher activity [49]. Kinetic studies on Pd-based catalysts showed a 0.5-1.0-order dependence for lower alkanes, whereas a very weak or zero-order dependence was observed for oxygen [50][51][52][53].…”
Section: Oxidation Of Methanementioning
confidence: 99%
“…Autothermal operation for the lower boundary of the range is only attainable by the more active precious-metal catalysts. The higher boundary of the range corresponds to studies where the heat extraction from the reactor was tested [42,[55][56][57][58]. This topic will be discussed in a separate section.…”
Section: Oxidation Of Methanementioning
confidence: 99%
See 3 more Smart Citations